PWM technique with variable carrier wave frequency to reduce switching loss in grid- connected pv inverter - Tran Quang Tho; Truong Viet Anh; Le Minh Phuong (Journal of Technical Education Science, 2014)
The increasing application of distributed power generations into the power system leads to a grid interconnection requirements of THD stricter and stricter. The reduction of current THD of grid-connected inverters to satisfy the grid code by increasing of switching frequency in PWM of inverters is one of popular methods but increases switching loss. The aim of this paper is to propose a PWM technique with variable switching frequency to reduce switching loss in inverters. The simulation results of a grid-connected inverter system in Matlab/Simulink show that the switching loss of the proposed technique is lower than the constant switching frequency.